2021
DOI: 10.18295/squmj.4.2021.040
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap in Online Learning Anxiety Among Different Generations in Health Professions Education

Abstract: Objective: The current study aimed to examine the effects of the generation group that individuals belonged to, on anxiety with respect to online learning among students and online learning and teaching activities among faculty. Methods: A cross-sectional study was conducted using the Online Course Anxiety Scale in April 2020. The responses were stratified by generations, and SPSS was used for statistical analysis. Results: The response rate was 97.8% and 86.4% for students and faculty, respectively. Only 5.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Some studies suggest users with high anxiety might show increased online interactions (Dutta et al, 2018), which may not hold true or even be misleading in the online learning context. Our results further provide opportunities to improve the understanding of the role of anxiety in the online learning process, which also offers insights to integrate the disconnected and conflicting views in prior studies (Elshami et al, 2021; Gangaiamaran & Pasupathi, 2017; Warner et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Some studies suggest users with high anxiety might show increased online interactions (Dutta et al, 2018), which may not hold true or even be misleading in the online learning context. Our results further provide opportunities to improve the understanding of the role of anxiety in the online learning process, which also offers insights to integrate the disconnected and conflicting views in prior studies (Elshami et al, 2021; Gangaiamaran & Pasupathi, 2017; Warner et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…Prior studies suggested that people with higher anxiety may feel pressure, which results in the decline of learning behaviour (Peltier et al, 2021). For example, prior studies demonstrated that anxiety negatively predicted the students' language achievement (Zheng & Cheng, 2018) and the e‐learning process (Elshami et al, 2021; Warner et al, 2020). Our results further confirmed that a significant difference in learning outcomes occurs even if these learners maintain the same volume of online learning activities (No significant direct effect of anxiety on learning habit was found in our study).…”
Section: Discussionmentioning
confidence: 99%
“…The items illustrate the features of relaxed feelings in learning, testing, and using technology online, and being confident in language competence. Likewise, previous studies indicate that students who had prior online experiences experienced less anxiety (Elshami et al, 2021;Pichette, 2009). The findings showed that while some students had anxiety in online learning, their counterparts had positive feelings in online learning and enjoyed it.…”
Section: Discussionsupporting
confidence: 53%
“…Likewise, the Thai university students had a significant level of the online learning anxiety (Chimwong, 2020). The samples in this study are aged between 19 and 22, categorized as a Generation Z (born after 1997) group, who mostly experienced anxiety during online learning, specifically when they had online discussions and written communication (Elshami et al, 2021). In the current study, the EFL students' possible levels of online learning anxiety were evaluated by the pre-screening online questionnaire.…”
Section: Online Learning Anxietymentioning
confidence: 99%
“…Changes in social media, along with developments in how people access the internet using gadgets or smartphones that can easily be accessed anytime and anywhere, means that every day people encounter promotions on social media carried out by marketers [42][43][44]. This emerging potential will be even more tremendous when targeting and reaching the generation of Millennials and Gen Xennials through online channels or via the internet [45,46].…”
Section: Introductionmentioning
confidence: 99%